2015
DOI: 10.18632/oncotarget.6284
|View full text |Cite
|
Sign up to set email alerts
|

A double feedback loop mediated by microRNA-23a/27a/24-2 regulates M1versusM2 macrophage polarization and thus regulates cancer progression

Abstract: In response to microenvironmental signals, macrophages undergo different types of activation, including the “classic” pro-inflammatory phenotype (also called M1) and the “alternative” anti-inflammatory phenotype (also called M2). Macrophage polarized activation has profound effects on immune and inflammatory responses, but mechanisms underlying the various types of macrophage is still in its infancy. In this study, we reported that M1-type stimulation could down-regulate miR-23a/27a/24-2 cluster transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 56 publications
8
86
1
Order By: Relevance
“…This cluster is downregulated during M1 polarization by NF‐κB binding to the cluster promoter. However, miR‐23a has been also reported to promote NF‐κB signaling via the NF‐κB pathway inhibitor A20, a zinc‐finger protein encoded by the TNFAIP3 gene . The expression of miR‐23a is inhibited by melatonin, which, thereby, attenuates the inflammatory response (Figure C) .…”
Section: Mechanisms Whereby Melatonin Regulates Macrophage Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This cluster is downregulated during M1 polarization by NF‐κB binding to the cluster promoter. However, miR‐23a has been also reported to promote NF‐κB signaling via the NF‐κB pathway inhibitor A20, a zinc‐finger protein encoded by the TNFAIP3 gene . The expression of miR‐23a is inhibited by melatonin, which, thereby, attenuates the inflammatory response (Figure C) .…”
Section: Mechanisms Whereby Melatonin Regulates Macrophage Polarizationmentioning
confidence: 99%
“…STAT‐6 activates miR‐23a/miR‐27a/miR‐24‐2 transcription by binding to the cluster promoter during M2 polarization. In a negative feedback loop, miR‐23a inhibits the formation of M2 cytokines via directly targeting JAK1 and STAT‐6 . The jointly regulated miR‐27a acts in parallel by downregulating IRF4 and PPAR‐γ .…”
Section: Mechanisms Whereby Melatonin Regulates Macrophage Polarizationmentioning
confidence: 99%
“…miR-155 was also reported to activate STAT3 signaling and promote breast cancer cells (BCC) progression [40,41]. miR-23a/24-2/27a modulate macrophage polarization in BCC through the Janus kinase (JAK)/STAT pathway [48]. miRNAs indirect regulation of PD-L1 expression miRNAs indirectly modulate the PD-L1 expression through the epigenetic regulation of upstream signaling pathways such as phosphatase and tensin homolog (PTEN)/PI3K/Akt and signal transducer and activator of transcription (STAT).…”
Section: Mirnas Direct Regulation Of Pd-l1 Expressionmentioning
confidence: 99%
“…Recent studies found that miRNAs have critical role in both innate and adoptive immune response [140], such as macrophage polarization, T cell and B cell differentiation [141]. The role of miRNAs has been investigated in the regulation of IL-10 and its related pathways in immune modulating cells [142, 143]. Feng et al, [144] demonstrated that miR-466 l up-regulate IL-10 expression in TLR-triggered macrophages both at mRNA and protein levels.…”
Section: The Role Of Mirna In Regulation Of Il-10 and Other Signallinmentioning
confidence: 99%
“…As reported by Ouiment and colleagues that, miR-33 promote M1 phenotype by up-regulating the expression of M1 markers such as Il6 , Nos2 , and Il1b, while reduced the expression of the M2 macrophages markers, Mrc1 (mannose receptor CD206) and Fizz1/Retnla [152]. Sisi et al, [143] reported that miR-23a and 27a inhibit the polerization of M2 phenotype while promote M1 phenotype by targeting 3UTR of JAK1/STAT6 and IRF4/PPAR-γ. The cluster of miR-23a/27a/24-2 enhance the production of inflammatory mediators (IL-1b, IL-6, IL-12 and TNF-a) while inhibit anti-inflammatory cytokine such as IL-10 [144].…”
Section: The Role Of Mirna In Regulation Of Il-10 and Other Signallinmentioning
confidence: 99%